Time Series Analysis of Heavy Metal Concentrations along the Watershed Gradient in Cameron Highlands: Geospatial Approaches - Haron S.H.; Ismail B.S.; Mispan M.R.; Rahman N.F.A.; Khalid K.; Abdul Rasid M.Z.; Sidek L.M. (Institute of Physics Publishing, 2023)
Agriculture; Arsenic; Health risks; Heavy metals; Inductively coupled plasma; Rivers; Sediments; Time series analysis; Agricultural areas; Heavy metal concentration; Inductively coupled plasma (ICP); Inverse distance weighting; Metal concentrations; Sample concentration; Spatial interpolation; Toxic heavy metals; Cadmium; accumulation; concentration (composition); data set; fluvial deposit; heavy metal; pollution monitoring; polygon; sampling; seasonal variation; sediment pollution; time series analysis; toxicity; watershed; Cameron Highlands; Malaysia; Pahang; West Malaysia